Germany and the role of nuclear weapons: Between prohibition and revival - Oliver Meier (Stiftung Wissenschaft und Politik (SWP), 2016)
Never since the end of the Cold War have the international community and Europe been so deeply divided over the role of nuclear weapons in security policy. There is disagreement within the United Nations over whether to begin negotiations on a treaty banning nuclear weapons. At the same time, Russia's aggression against Ukraine and Moscow's associated nuclear threats have triggered a new discussion in NATO about enhancing its nuclear deterrent. Both debates are difficult and uncomfortable for Berlin, because they undermine the incremental arms control approach favoured by Germany. Against the background of the upcoming July 2016 NATO summit in Warsaw and the forthcoming establishment of a working group on nuclear disarmament in Geneva, Berlin must adopt a clear stance on nuclear deterrence if it is to play an active role in shaping the outcome of these discussions. (SWP Comments)
Keywords: 320